To build the enterprise's image as an important instrument in market competition - Tkachuk (Stakhurska), Svitlana (My University, 2013)
The basic elements of firm's style as the main instrument of firm's image forming are examined, the methods of product's positioning on market, including the process of decision making about advertising campaign, are analyzed.
Keywords: імідж підприємства; реклама; фірмовий стиль; торгова марка; фірмовий логотип; имидж предприятия; фирмовый стиль; торговая марка; реклама; фирмовый логотип; enterprise's image; publicity; firm style; trade mark; firm logotype; кафедра маркетингу